2016
DOI: 10.5901/mjss.2016.v7n3s1p222
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Political Influence and Youth’s Leadership Participation in Malaysia: A Conceptual Model Extending TPB

Abstract: The study seeks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Some scholars proved that intention is predicted by other variables like moral norms (Botetzagias et al, 2015;De Leeuw et al, 2015). Additionally, intentions are predicted with socio-cultural influence and self-identity (Ekpe et al, 2016;Shaw and Shiu, 2013). Despite expanding the TPB model to enhance the understanding and prediction of intentions and subsequent behaviours by past studies referenced above, such evidence of incorporating TIN as a critical investment factor that could support individual investment intention formation is currently lacking.…”
Section: Literature Review and Hypotheses Development 21 Investment I...mentioning
confidence: 99%
“…Some scholars proved that intention is predicted by other variables like moral norms (Botetzagias et al, 2015;De Leeuw et al, 2015). Additionally, intentions are predicted with socio-cultural influence and self-identity (Ekpe et al, 2016;Shaw and Shiu, 2013). Despite expanding the TPB model to enhance the understanding and prediction of intentions and subsequent behaviours by past studies referenced above, such evidence of incorporating TIN as a critical investment factor that could support individual investment intention formation is currently lacking.…”
Section: Literature Review and Hypotheses Development 21 Investment I...mentioning
confidence: 99%
“…Other scholars (e.g. Ekpe, Mohamad, Mat, & Simpong, 2016) found that behavioural intentions are also determined by socio-cultural influence and selfidentity (Shaw & Shiu, 2013). While the extension to the TPB theory had improved the understanding and prediction of behaviour, previous studies noted above had assumed that behaviour is guided by reasoned considerations.…”
Section: Past Behavioural Biases Attitude Toward Behaviour and Stockmentioning
confidence: 99%